Environmental complexity and predator density mediate a stable earwig-woolly apple aphid interaction - Robert Bischoff; Prayan Pokharel; Paul Miedtke; Hans-Peter Piepho; Georg Petschenka (Basic and Applied Ecology, 2024)
Regulation of insect pests by predators is an integral component of biological pest control. However, predator-prey interactions often reach a stable state leading to coexistence, which can be problematic for plant protection if the persisting herbivores exceed a damage threshold. Consequently, understanding the factors mediating this stability is crucial for successful biocontrol. Here, we investigated the predator-prey interaction of an important apple pest, the woolly apple aphid (WAA) (Eriosoma lanigerum Hausm.) (Hemiptera: Aphididae), and its predator, the omnivorous common earwig (Forficula auricularia L.) (Dermaptera: Forficulidae). To this end, we introduced increasing densities of earwigs in gauze-bagged branches harbouring defined amounts of WAA and recorded predation on individual WAA colonies for almost one month. We showed that the spatial complexity of the predation environment and the earwig density determined the predation efficiency on WAAs. Earwigs could eradicate WAAs regardless of density on short apple branches without lateral twigs (first trial). However, on longer, more complex branches (second trial), stable states of WAAs and earwigs were observed. Only the highest earwig density could completely consume WAA regardless of branch complexity. We introduce a conceptual model to describe the searching capability of earwigs, which determines their efficiency in locating prey. Our model predicts that searching capability is reduced by environmental complexity; this effect is alleviated by increased earwig density, as more predators possess a higher searching capability. Conclusively, our model explains why only the highest earwig density could completely consume WAA irrespective of complexity and illustrates how predator density and environmental complexity jointly influence predation. Thus environmental characteristics not inherent to our predator-prey interaction were a decisive factor for effective predation on gauze-bagged branches. Based on these results, reducing tree complexity by pruning or augmenting earwig populations in orchards can increase biocontrol of the WAA.